2017
DOI: 10.3390/ijms19010109
|View full text |Cite
|
Sign up to set email alerts
|

Liver Graft Susceptibility during Static Cold Storage and Dynamic Machine Perfusion: DCD versus Fatty Livers

Abstract: We compared static preservation (cold storage, CS, 4 °C) with dynamic preservation (machine perfusion, MP, 20 °C) followed by reperfusion using marginal livers: a model of donation after cardiac death (DCD) livers and two models of fatty livers, the methionine-choline deficient (MCD) diet model, and obese Zucker (fa/fa) rats. CS injury in DCD livers was reversed by an oxygenated washout (OW): hepatic damage, bile flow, and the ATP/ADP ratio in the OW + CS group was comparable with the ratio obtained with MP. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…It was suggested that subnormothermic temperatures may bridge the gap between metabolic retardation during cold hypothermia and hypoxia at 'hotter' normal physiological temperatures, enabling the maintenance of an approximate 25% of physiological metabolic levels in the liver graft [37]. In a number of animal and preclinical studies [18,[27][28][29][30]38,39] assessing the effects on resynthesis of tissue ATP by SNMP on livers of different extended criteria, DBD or DCD and steatosis were identified (Tables 2-4). Additionally, there are studies of a relatively new perfusion technique, controlled oxygenated rewarming (COR) developed by Minor et al [18] in Essen, Germany.…”
Section: Positive Effects Of Subnormothermic Perfusion Temperatures (mentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that subnormothermic temperatures may bridge the gap between metabolic retardation during cold hypothermia and hypoxia at 'hotter' normal physiological temperatures, enabling the maintenance of an approximate 25% of physiological metabolic levels in the liver graft [37]. In a number of animal and preclinical studies [18,[27][28][29][30]38,39] assessing the effects on resynthesis of tissue ATP by SNMP on livers of different extended criteria, DBD or DCD and steatosis were identified (Tables 2-4). Additionally, there are studies of a relatively new perfusion technique, controlled oxygenated rewarming (COR) developed by Minor et al [18] in Essen, Germany.…”
Section: Positive Effects Of Subnormothermic Perfusion Temperatures (mentioning
confidence: 99%
“…Ferrigno [22] Rat, DCD Berendsen [23] Rat, DCD Bruinsma [24] Rat Minor (COR20) [18] Porcine Bruinsma [25] Human, DBD, DCD Ferrigno (20 > 10 > 30 > 37 • C) [24] Rat Bruinsma (DBD/DCD/ steatotic livers) [25] Human von Horn (COR 20 • C > COR 35 • C) [28] Rat, DCD Okamura [39] Rat, steatotic livers Ferrigno [27] Rat, DCD, steatotic livers In the kidneys (Table 12), with fewer published literature on SNMP and NMP to date, HOPE appeared to be most effective in increasing graft ATP resynthesis. Buchs [44] Porcine, DCD Lazeyras [45] Porcine, DCD Ravaioli [47] Human, DBD More evidence is needed on the effects of preservation temperature on donor pancreatic ATP levels (Table 13).…”
mentioning
confidence: 99%
“…SNMP and NMP significantly ameliorated hepatic damage in DCD livers compared to SCS in animal models (31,39,60,65,68,72). In a porcine model of liver MP, prolonged periods of NMP facilitate a reduction in hepatic steatosis (63), while the supplementation of perfusate with defatting agents significantly reduced the intracellular fat content of perfused rat livers within a few hours (59).…”
Section: Subnormothermic/normothermic Machine Perfusion Techniquesmentioning
confidence: 96%
“…Therefore, DCD livers have higher risk of early postoperative allograft dysfunction, primary nonfunction, ischemic cholangiopathy, and vascular embolism than DBD livers, greatly affecting donor liver survival and patient prognosis (Angelico et al 2018 ; DeOliveira et al 2011 ); these problems have not been resolved. Static cold storage (SCS) is subject to some limitations for preserving DCD livers, which may not have sufficient physiological reserves for tolerating SCS-related damage; liver energy metabolism and mitochondrial function are easily impaired, and are particularly sensitive to SCS-related IRI; accordingly, SCS exposure should be restricted (Detelich and Markmann 2018a ; Ferrigno et al 2017 ). Normothermic machine perfusion (NMP) can simulate the normal metabolic state in vivo, can reveal the quality of the liver by assessing bile production and lactate clearance, and store and repair donor livers.…”
Section: Introductionmentioning
confidence: 99%